A review study of the current research on energy hub for energy positive neighborhoods. (September 2017) - Walker, Shalika; Labeodan, Timilehin; Maassen, Wim; Zeiler, Wim
Abstract: Energy positive neighborhoods and cities are emerging concepts aimed at addressing the current energy and environmental sustainability challenges. In this paper, the concept and current research on energy hubs relating to energy positive neighborhoods are presented. In addition to discussing advantages and challenges of energy positive neighborhoods and energy hubs, opportunities for future research and development are also conversed.